2000
DOI: 10.4049/jimmunol.165.12.7240
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TNF-α and IL-1 Blockade in Collagen-Induced Arthritis and Comparison with Combined Anti-TNF-α/Anti-CD4 Therapy

Abstract: We have evaluated the effects of anti-TNF-α, anti-IL-1, and combined anti-TNF-α/anti-CD4 therapy in collagen-induced arthritis. Blockade of TNF-α or IL-1 before disease onset delayed, but did not prevent, the induction of arthritis. When treatment was initiated after onset of arthritis, anti-TNF-α, anti-IL-1β, and anti-IL-1R (which blocks IL-1α and IL-1β) were all found to be effective in reducing the severity of arthritis, with anti-IL-1R and anti-IL-1β showing greater efficacy than anti-TNF-α. Anti-IL-1β was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 33 publications
9
61
0
Order By: Relevance
“…The tolerogenic DCs used by those investigators, which were generated by short-term LPS treatment, also inhibited established arthritis without changing the IgG2a:IgG1 ratio; however, their tolerogenic DC treatment did inhibit IFN␥ production (30). Earlier studies of anti-TNF treatment of established arthritis also did not show a change in the IgG2a:IgG1 ratio (41,42). It could therefore be contended that a reduction of type II collagen-specific IgG2a is important for the prevention of arthritis but may be of less importance after disease onset.…”
Section: Discussionmentioning
confidence: 96%
“…The tolerogenic DCs used by those investigators, which were generated by short-term LPS treatment, also inhibited established arthritis without changing the IgG2a:IgG1 ratio; however, their tolerogenic DC treatment did inhibit IFN␥ production (30). Earlier studies of anti-TNF treatment of established arthritis also did not show a change in the IgG2a:IgG1 ratio (41,42). It could therefore be contended that a reduction of type II collagen-specific IgG2a is important for the prevention of arthritis but may be of less importance after disease onset.…”
Section: Discussionmentioning
confidence: 96%
“…Combined anti-TNFα/anti CD4 therapy suppressed both TNFα and IL-1β expression in the DBA/1 CIA mouse model. In addition, this combined therapy also caused the normalization of serum amyloid P levels [60]. In a separate study, anti-TNFα blockade, but not anti-CD4 Abs, significantly reduced the frequency of cells expressing TNFα, IL-1β, VLA-4, VCAM-1 and CD4 + Tcells and macrophages in the joint of CIA-induced mice model [61].…”
Section: Mechanistic Lessons From Animal Modelsmentioning
confidence: 89%
“…Previously, we and others have shown that TNF blockade during the induction phase of CIA delays the onset of arthritis and reduces its subsequent clinical severity (12)(13)(14). To evaluate the possible role played by TNF in the subclinical changes observed in this study, mice were immunized on day 0 with CFA alone, then injected intraperitoneally with 300 g of anti-TNF mAb (TN3-19.12) or PBS (6 animals in each group) on days 7, 9, and 11.…”
Section: Resultsmentioning
confidence: 99%